A portable electroantennogram recorder for laboratory and field measurements of semiochemicals - Rosa, Bruno Miguel Contente (2019)
Electroantennography is a bioassay technique used to study the olfactory responses of insects. This technique allows for the identification of semiochemicals that mediate insect behavior and reproduction, thus making it one of the key research tools for environmentally friendly pest control methods. It is common practice to interface the insect antennae with micropipette Ag/AgCl electrodes supported on micro-manipulators and to amplify the signals resulting from the perception of the olfactory stimuli, through high gain differential amplifiers. This approach has been routinely used under laboratory conditions, yet the size and nature of the required apparatus and amplification equipment makes it impractical for field measurements. This project explores the use of modern delta-sigma analog to digital converters specifically designed for the measurement of biopotential signals, focusing on the miniaturization of the acquisition, processing and digitalization electronics. The design and a prototype of a device with autonomous air pumping, air distribution valve and a dual antenna support are presented, allowing for the simultaneous measurement of the signals of both insect antennae. The proposed antennae holder contains reservoirs for liquid or gel electrolytes and Ag/AgCl electrodes. The support is detachable, allowing easy insertion of excised antennae. 3D printed parts were used for the construction of the mechanical supports and insect antennae holder. The device has an envelope of 123x60.5x46.4 mm and is battery powered. The acquired antennal data is transmitted to a laptop computer via a USB connection. Applications of this device range from the identification of semiochemicals used in pest management programs to bio-sensor development and evaluation. Noise and linearity characterization of the device was performed and the olfactory responses of the eucalyptus weevil, Gonipterus platensis (Coleoptera curculionidae) to verbenone were successfully measured. The results obtained are discussed.